Temporal Variation of Soil Gas Radon Associated with Seismic Activity: A Case Study in NW Greece - C. Papachristodoulou; K. Stamoulis; K. Ioannides (Pure and Applied Geophysics, 2020)

Assemblage-level effects of the introduced peacock hind (Cephalopholis argus) on Hawaiian reef fishes - J. L. Giddens; C. Wiggins; A. M. Friedlander; E. J. Conklin; K. A. Stamoulis; D. Minton (Environmental Biology of Fishes, 2018)

“New Mediterranean Biodiversity Records” (March 2017) - L. LIPEJ; I. ACEVEDO; E.H.K. AKEL; A. ANASTASOPOULOU; A. ANGELIDIS; E. AZZURRO; L. CASTRIOTA; M. ÇELIK; L. CILENTI; F. CROCETTA; A. DEIDUN; A. DOGRAMMATZI; et al. (Mediterranean Marine Science, 2017)
This Collective Article presents information on 22 species belonging to 5 Phyla, arranged geographically from from west to east. The new records were found in 8 countries as follows: Spain: first record of the two scarcely known nemerteans Baseodiscus delineatus and Notospermus geniculatus in Formentera; Malta: second record of the alien fish Lagocephalus sceleratus; Italy: the alien polychaete Syllis pectinans and the isopod Paranthura japonica, as well as the cryptogenic opisthobranch Anteaeolidiella lurana, were found in the fouling assemblages along the docks of the port of Livorno. New decapod records are reported from Sicily (the alien Callinectes sapidus and the native Pachygrapsus maurus) and Apulia (Percnon gibbosus and Procambarus clarkii); the lesser amberjack Seriola fasciata extended its geographical range to the Egadi Isands and Siganus luridus was documented for the first time along the Ionian coasts of Apulia and Calabria. Slovenia: the first record of the alien bivalve Brachidontes pharaonis is reported, together with a survey of up to date Adriatic records. Greece: the first record of the gastropod Rhinoclavis kochi is reported from Gavdos island. In addition, two records of endangered and rare cartilaginous fish were reported, namely, the shark Hexanchus griseus and the ray Leucoraja fullonica, as well as additional records of Siganus luridus for Lesvos and Malleus regula and Fulvia fragilis from Astypalaia. Turkey: the black wing flyingfish Hirundichthys rondeletii is reported for the very first time from the Black Sea. Egypt: the Indo-Pacific crab Halimede ochtodes is reported as established in Port Said. In addition, biometric parameters and meristic counts are reported for Anthias anthias in Damietta. Cyprus: the alien opisthobranch gastropod Bursatella leachii is reported for first time.

New Mediterranean Biodiversity Records (July 2016) - T. DAILIANIS; O. AKYOL; N. BABALI; M. BARICHE; F. CROCETTA; V. GEROVASILEIOU; R. CHANEM; M. GÖKOĞLU; T. HASIOTIS; A. IZQUIERDO-MUÑOZ; D. JULIAN; S. KATSANEVAKIS; et al. (Mediterranean Marine Science, 2016)
This contribution forms part of a series of collective articles published regularly in Mediterranean Marine Science that report on new biodiversity records from the Mediterranean basin. The current article presents 51 geographically distinct records for 21 taxa belonging to 6 Phyla, extending from the western Mediterranean to the Levantine. The new records, per country, are as follows: Spain: the cryptogenic calcareous sponge Paraleucilla magna is reported from a new location in the Alicante region. Algeria: the rare Atlanto-Mediterranean bivalve Cardium indicum is reported from Annaba. Tunisia: new distribution records for the Indo-Pacific lionfish Pterois miles from Zembra Island and Cape Bon. Italy: the ark clam Anadara transversa is reported from mussel cultures in the Gulf of Naples, while the amphipod Caprella scaura and the isopods Paracerceis sculpta and Paranthura japonica are reported as associated to the –also allochthonous–bryozoan Amathia verticillata in the Adriatic Sea; in the latter region, the cosmopolitan Atlantic tripletail Lobotes surinamensisis also reported, a rare finding for the Mediterranean. Slovenia: a new record of the non-indigenous nudibranch Polycera hedgpethi in the Adriatic. Greece: several new reports of the introduced scleractinian Oculina patagonica, the fangtooth moray Enchelycore anatina, the blunthead puffer Sphoeroides pachygaster (all Atlantic), and the lionfish Pterois miles (Indo-Pacific) suggest their ongoing establishment in the Aegean Sea; the deepest bathymetric record of the invasive alga Caulerpa cylindracea in the Mediterranean Sea is also registered in the Kyklades, at depths exceeding 70 m. Turkey: new distribution records for two non indigenous crustaceans, the blue crab Callinectes sapidus (Atlantic origin) and the moon crab Matuta victor (Indo-Pacific origin) from the Bay of Izmir and Antalya, respectively; in the latter region, the Red Sea goatfish Parupeneus forsskali, is also reported. Lebanon: an array of records of 5 alien and one native Mediterranean species is reported by citizen-scientists; the Pacific jellyfish Phyllorhiza punctata and the Indo-Pacific teleosteans Tylerius spinosissimus, Ostracion cubicus, and Lutjanus argentimaculatus are reported from the Lebanese coast, the latter notably being the second record for the species in the Mediterranean Sea since 1977; the native sand snake-eel Ophisurus serpens, rare in the eastern Mediterranean, is reported for the first time from Lebanon, this being its easternmost distribution range; finally, a substantial number of sightings of the lionfish Pterois miles further confirm the current establishment of this lessepsian species in the Levantine.

New Mediterranean Biodiversity Records (March 2016) - P. K. KARACHLE; A. ANGELIDIS; G. APOSTOLOPOULOS; D. AYAS; M. BALLESTEROS; C. BONNICI; M. M. BRODERSEN; L. CASTRIOTA; N. CHALARI; J. M. COTTALORDA; F. CROCETTA; A. DEIDUN; et al. (Mediterranean Marine Science, 2016)
In this Collective Article on “New Mediterranean Biodiversity Records”, we present additional records of species found in the Mediterranean Sea. These records refer to eight different countries throughout the northern part of the basin, and include 28 species, belonging to five phyla. The findings per country include the following species: Spain: Callinectes sapidus and Chelidonura fulvipunctata; Monaco: Aplysia dactylomela; Italy: Charybdis (Charybdis) feriata, Carcharodon carcharias, Seriola fasciata, and Siganus rivulatus; Malta: Pomacanthus asfur; Croatia: Lagocephalus sceleratus and Pomadasys incisus; Montenegro: Lagocephalus sceleratus; Greece: Amathia (Zoobotryon) verticillata, Atys cf. macandrewii, Cerithium scabridum, Chama pacifica, Dendostrea cf. folium, Ergalatax junionae, Septifer cumingii, Syphonota geographica, Syrnola fasciata, Oxyurichthys petersi, Scarus ghobban, Scorpaena maderensis, Solea aegyptiaca and Upeneus pori; Turkey: Lobotes surinamensis, Ruvettus pretiosus and Ophiocten abyssicolum. In the current article, the presence of Taractes rubescens (Jordan & Evermann, 1887) is recorded for the first time in the Mediterranean from Italy. The great contribution of citizen scientists in monitoring biodiversity records is reflected herein, as 10% of the authors are citizen scientists, and contributed 37.5% of the new findings.

Distribution of heavy metals in sediment cores of Lake Pamvotis (Greece): a pollution and potential risk assessment - K. Ioannides; K. Stamoulis; C. Papachristodoulou; E. Tziamou; C. Markantonaki; I. Tsodoulos (Environmental Monitoring and Assessment, 2015)